Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1121/1.424358
|View full text |Cite
|
Sign up to set email alerts
|

Ground effect over hard rough surfaces

Abstract: Laboratory and outdoor measurements are reported of the relative sound pressure level spectrum over hard surfaces containing either random or periodically spaced arrays of 2-D roughnesses. The resulting data have been compared with predictions obtained analytically and with numerical predictions of a boundary element code. Effective impedances of the rough surfaces have been calculated from the boss theory developed by Twersky. A classical asymptotic approximation for propagation near grazing incidence from a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…there is significant coherent scattering and reflection) there can be a significant change in ground effect. Many laboratory experiments have shown that the influence of small scale roughness on propagation over hard and soft surfaces can be considered in terms of effective surface impedance [38][39][40]91,92]. Particularly if the surface is acoustically-hard, roughness induces a surface wave.…”
Section: Ground Rougheningmentioning
confidence: 99%
See 1 more Smart Citation
“…there is significant coherent scattering and reflection) there can be a significant change in ground effect. Many laboratory experiments have shown that the influence of small scale roughness on propagation over hard and soft surfaces can be considered in terms of effective surface impedance [38][39][40]91,92]. Particularly if the surface is acoustically-hard, roughness induces a surface wave.…”
Section: Ground Rougheningmentioning
confidence: 99%
“…The latter corresponds to effectively making a surface acoustically softer [38][39][40] (see also Section 4.3). Starting from a symmetric trapezoidal berm (15 m wide, 4 m high, with a 3-m wide top), consisting of compacted earth (represented by a flow resistivity of 300 kPa s/m 2 ), positioned near a 4-lane road with mixed traffic, various roughening approaches were numerically studied in Ref.…”
Section: Berm Rougheningmentioning
confidence: 99%
“…There is considerable laboratory data showing that the effect of adding small scale roughness to a surface, whatever its original impedance, is to modify its apparent impedance [2,[28][29][30][31][32]. If the original smooth surface is acoustically-hard then the effective impedance of the roughened surface is finite.…”
Section: Laboratory Data On 2d Rough Surfacesmentioning
confidence: 99%
“…there is significant coherent scattering and specular reflection) there can be a significant change in ground effect. Many laboratory experiments show that the influence of small scale roughness on propagation over hard and soft surfaces can be considered in terms of effective surface impedance [2,[28][29][30][31][32]. Also, particularly if the surface is acoustically-hard, roughness induces a surface wave.…”
Section: D Roughnessmentioning
confidence: 99%
“…This problem has attracted much attention in the literature (see, for example, [17,30,31,16,21,6,48]), both in its own right and also as a model of the scattering of an incident acoustic or electromagnetic wave by an infinite rough surface [8,47,36,7]. In the case in which there is no variation in the acoustical properties of the surface or the incident field in some fixed direction parallel to the surface, the problem is effectively twodimensional.…”
mentioning
confidence: 99%